ANALISIS SOAL-SOAL PENILAIAN HARIAN DALAM LKS MATA PELAJARAN MATEMATIKA SMA TERBITAN PT PENERBIT INTAN PARIWARA BERDASARKAN TAKSONOMI BLOOM REVISI - Zuhri Fatihatu Rohmah; Budiyono Budiyono; Waryanti Ika Purwaningsih (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
This research aims to describe the cognitive level and the percentage of daily assessment multiple choices on worksheet Mathematics subjects in class XI semester 1 semester based on Bloom's revised Taxonomy. The number of questions analyzed is 34 questions out of 149 multiple choice questions. The cognitive level of Bloom's revised Taxonomy includes the processes of remembering (C1), understanding (C2), applying (C3), analyzing (C4), evaluating (C5), and creating (C6). The type of research used is descriptive qualitative content analysis techniques. The data source in this study is a multiple choice daily assessment on the LKS mathematics subjects in class XI semester 1 published by PT Publit Intan Pariwara. Data collection techniques in this study is documentation. The documents used were daily assessment questions on the first semester XI high school mathematics LKS published by PT Publisher Intan Pariwara and the revised Bloom Taxonomy cognitive level. The data technique used are Miles and Hubermen model. The results of the analysis show that the cognitive level of questions in the LKS Mathematics High School subjects based on the cognitive level of understanding (C2) as many as 18 (52.94%) questions, applying (C3) as many as 12 (35.29%) questions, analyzing (C4) as many as 4 (12.12%) questions, and at the cognitive level remembering (C1), evaluating (C2), and creating (C6) there were no problems at this cognitive level. So that it can be seen that the daily assessment questions is not fulfilled the cognitive level of Bloom Taxonomy so there is a need for training in compiling questions in the worksheet in order to cover all cognitive levels of the revised Bloom Taxonomy and the learning objectives are achieved